ACCOUNTING TREATMENT ON LEASING TRANSACTION AND ITS IMPACT TOWARD COST ACCOUNTING AND FINANCIAL REPORTING OF CEMENT COMPANY - Ringgonandyo Isnubroto; Agung Juliarto (Diponegoro Journal of Accounting, 2021)
There are many business sectors around the world. Of course, each of these sectors has the same goal, namely to generate profits and meet the needs of every consumer. The cement industry is one industry that is quite strong and growing compared to other industries. The company certainly has a long-term plan to be able to achieve the vision and mission that has been determined. Therefore, the company strives to have the assets needed for operational reasons. These assets are obtained from investing or financing activities. One way to get assets is to make lease transactions. Each lease transaction must be recognized and recorded by the company. PSAK 73 has become the company's guideline in recording and recognizing lease accounting since January 1, 2020. This encourages the company to make appropriate accounting treatments to implement these standards. The aim of this research is to examine the accounting treatment of leasing transactions as a result of the adoption of PSAK 73 in a cement company. The researcher also proposes examining the influence of this adoption on financial reporting and cost accounting. To conduct this study, the researcher employed a literature review strategy, relying on papers and journals as a foundation.